Land-use Planning for Conservation, Management and Development of Land and Water Resources in Arunachal Pradesh - Mahalanobis, J.K.; Adak, N.K. (Journal of Soil and Water Conservation, 2022)
The existing land-use pattern in the state is fast changing tinder the impact of various development programmes. However, land-use planning should ensure every piece of land to be put under proper use to which it is best suited. Though in the state of Arunachal Pradesh the land resources required for agricultural purposes are limited, planning for its better use is a must for intensive cultivation as well as sustained increase in production. There should be continuous assessment of the status of land-use and its productivity vis-a-vis socio-economic condition of the people to evolve a rational land-use policy in the state.